2019
DOI: 10.3390/ijerph16040645
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors Influencing the Use of eHealth in People with Chronic Diseases

Abstract: Alongside the growing number of older persons, the prevalence of chronic diseases is increasing, leading to higher pressure on health care services. eHealth is considered a solution for better and more efficient health care. However, not every patient is able to use eHealth, for several reasons. This study aims to provide an overview of: (1) sociodemographic factors that influence the use of eHealth; and (2) suggest directions for interventions that will improve the use of eHealth in patients with chronic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
152
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(196 citation statements)
references
References 39 publications
(148 reference statements)
15
152
2
5
Order By: Relevance
“…This might have resulted in feeling more supported and motivated to engage in healthier behavior these first months, suggesting that blended care is the way forward for this patient population. 20 Regarding sleep efficiency, no improvement was observed. The majority of previous studies that found positive associations between lifestyle interventions and (self-reported) sleep quality in cardiac patients focused primarily on patients with obesity and established obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 95%
“…This might have resulted in feeling more supported and motivated to engage in healthier behavior these first months, suggesting that blended care is the way forward for this patient population. 20 Regarding sleep efficiency, no improvement was observed. The majority of previous studies that found positive associations between lifestyle interventions and (self-reported) sleep quality in cardiac patients focused primarily on patients with obesity and established obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 95%
“…Although there is a growing trend towards the use of mobile phones among the older generations [11], the elderly still prefer using computers compared to mobile phones, as the most recent study by Reiners et al [12] revealed is thanks to better technical aspects and access to the Internet. For example, more than half of the Italian and the German elderly reported they used the Internet to attain health-related information [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As a Swedish study [11] indicates, there are still feelings of ambivalence towards e-health among the elderly, especially in the area of mistrust in poor IT systems or impaired abilities to cope with technology. Therefore, the potential e-Health devices and their implementation should be targeted at the elderly people's needs and preferences [12,13]. Reiners et al [12] summarize these needs as follows:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The knowledge and attitude about the disease are influenced by many factors such as sociodemographic factors, media and the accessibility of health care services. 16 However, we must recognize the fact that the screening behavior of each individual is a twisted result of many factors at different levels. 17 Although there are several reports about cervical cancer screening in Iran, due to the geographical variation of the incidence/mortality of this disease, to conduct various studies from different regions of Iran leads to a more comprehensive report about the cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%